HUBUNGAN PERSEPSI MAHASISWA TENTANG PEMBIMBING KLINIK DENGAN PENCAPAIAN TARGET PRAKTEK KLINIK KEPERAWATAN MEDIKAL BEDAH DI BADAN LAYANAN UMUM RSUP PROF. DR. R.D. KANDOU MANADO - Janbonsel Bobaya; Maykel A. Kiling; Joice M. Laoh; Nancy Losu (Jurnal Ilmiah Perawat Manado (Juiperdo), 2015)
Nursing clinical practice is part of the curriculum that can not be separated from the theory, in which a nursing student to apply the concept of professional nursing. The success of the student in the clinical practice experience is influenced by several factors such as clinical instructor, the method used in the guidance clinic, completeness of facilities, as well as the cooperation of clients and families. This study aims to analyze the correlation between students' perceptions about clinical instructor with the achievement of medical-surgical nursing clinical practice in the Public Service Board Dr Prof. Dr. R. D. Kandou Manado. This type of research is cross-sectional. Based on the results of the bivariate analysis using Chi-square test found that the value of p = 0.101. The value of p> 0.05 indicates that there is no significant relationship between students' perceptions about the mastery of clinical instructor with the achievement of medical-surgical nursing clinical practice. P =0.046, p value <0.05 indicates that there is no significant relationship between students' perceptions of facilitators clinical instructor with the achievement of medical-surgical nursing clinical practice, the value of p = 0.109. The value of p> 0.05 indicates that there is no significant relationship between students' perceptions about the motivation clinical instructor with the achievement of medical-surgical nursing clinical practice, the value of p = 0.000. P value <0.05 indicates that there is a significant relationship between students' perceptions about clinical instructor communication with the achievement of medical-surgical nursing clinical practice, the value of p = 0.000. P value <0.05 indicates that there is a significant relationship between students' perceptions about clinical instructor supervision by the achievement of medical nursing clinical practice